Notes on the subspecies of Plagionotus arcuatus (Linnaeus, 1758) with description of a new subspecies from Iran (Coleoptera: Cerambycidae) - Królik, Roman; Kruszelnicki, Lech; Lasoń, Andrzej; Walczak, Marcin (Zootaxa, 2021)
This paper reviews the lower-ranked taxa within the species Plagionotus arcuatus (Linnaeus, 1758) and describes a new subspecies P. arcuatus shirazensis based on specimens from Iran. Some comments are made on the morphology of the subspecies, and a key, together with an exhaustive photographic documentation, is provided for their identification. The distribution ranges of these various taxa are discussed and basic biological information on all the subspecies is given. We explain our opposition to the subspecies Plagionotus arcuatus tastani Özdikmen, Atak & Uçkan, 2017, and have accordingly synonymized it with the nominative subspecies.